Frequenly Ask Question (FAQ) Chatbot for New Student Admission System Using Natural Language Processing at Politeknik Aisyiyah Pontianak - Safri Adam; Eliyana Lulianthy (Institut Bakti Nusantara, 2021)
CS (customer service) is a crucial part in an agency that deals with customers, including universities. Especially on the part of the new student admissions committee. However, the ability of CS handled by humans is very limited. In addition, the questions asked are often repeated. So we need an AI-based chatbot (Artificial intelligence) to answer questions from prospective new students. The purpose of this research is to design and build a chatbot system using NLP (natural language processing) to assist the CS of the new student admissions committee at Aisyiyah Polytechnic Pontianak in handling questions from prospective new students. This study uses the NLP method to recognize natural language input from the user. For the weighting of the answers using TF-IDF and cosine similarity. The chatbot system is implemented in the python programming language. The messaging application used is Telegram using the AIOGRAM library and BotFather as a provider of bots on Telegram. This research resulted in a chatbot application using Telegram which was built using the Python programming language and has been trained to recognize the natural language input from the user. From the test results obtained a recall rate of 88% and a precision of 66%. The chatbot application that was built can help the new student admissions committee in serving questions for prospective new students. The evaluation results show that the built chatbot is able to answer questions from users well.